1987
DOI: 10.1111/j.1432-1033.1987.tb13594.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of 2'-5' oligoadenylates in Escherichia coli

Abstract: The use of a highly specific radioimmunoassay and of HPLC permitted us to confirm the occurrence of 2′–5′ oligoadenylates [px(A2′p5′)nA] in several strains of Escherichia coli. Cellular concentrations of 2′–5′ oligoadenylates ranged from 50 nM to 300 nM. The mixture of 2′–5′ oligoadenylates consisted primarily of pppA2′p5′A, pA2′p5′A, A2′p5′Ap and A2′p5′A under normal conditions of growth. None of them activated R Nase L. Infection of the bacteria with the single‐stranded DNA phage M13 or induction of a heat‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The dsRNA required to produce 2-5A may be derived from pathogen or host RNAs; indeed, certain host mRNAs contain secondary structure that is capable of activating OAS (28). In addition, 2-5A linkages have been reported in bacteria (29) and RNase-L expression in bacteria results in cell RNA degradation and antiproliferative activity (30), suggesting that bacteria may produce endogenous activators of RNase-L. The validation of specific RNase-L substrates will provide a sensitive readout of its activity and a more physiologic system in which to dissect the source(s) of RNase-L activators in cells.…”
Section: Resultsmentioning
confidence: 99%
“…The dsRNA required to produce 2-5A may be derived from pathogen or host RNAs; indeed, certain host mRNAs contain secondary structure that is capable of activating OAS (28). In addition, 2-5A linkages have been reported in bacteria (29) and RNase-L expression in bacteria results in cell RNA degradation and antiproliferative activity (30), suggesting that bacteria may produce endogenous activators of RNase-L. The validation of specific RNase-L substrates will provide a sensitive readout of its activity and a more physiologic system in which to dissect the source(s) of RNase-L activators in cells.…”
Section: Resultsmentioning
confidence: 99%
“…The putative (2'-5')A,, synthetase was partially purified from tobacco and found to cross-react with human-(2'-5')A,, synthetase-reactive antibodies (Sela et a]., 1987). (2'-5')A, molecules were even detected in Escherichia coli (Trujillo et al, 1987) and in some other bacteria and yeasts (Laurence et al, 1984). However, this does not necessarily mean that the same pathway is involved in all cases.…”
mentioning
confidence: 99%
“…Furthermore, the isolated RNA species were not a lariat because they would have produced a different junction after digestion (i.e., a threeway junction). Moreover, the possibility that a 2Ј,5Ј-linked oligo(A) might have comigrated with PLMVd is highly unlikely, as it has been shown that most oligonucleotides of this type are usually very small (i.e., ϳ10 nt) (34). Also, it would be surprising for such an oligonucleotide to include a C/U dinucleotide and, more importantly, for this C/U dinucleotide to be the only 2Ј,5Ј-linked dinucleotide that it contains.…”
Section: Figmentioning
confidence: 99%